The Effect of Parents of The Parents on The Cooperative Level of Children Age 3-5 Years of Care Dental and Mouth in Blang Karieng Village District Nisam - Suriani; Rahmad Al-Hidayat (Talenta Publisher, 2019)
The problem of management of child behavior is a major problem in the practice of pediatric dentistry. One of the factors that influence the child's response to dental and oral care is parenting. In general, parenting is divided into three main categories, namely authoritarian parenting, permissive and democratic. The purpose of this study was to study the effect of parenting on the cooperative level of children aged 3-5 years in dental and oral care. This study was an analytic observational study with a cross sectional research design. Population is the total number of subjects studied. The population in this study were all children aged 3-5 years in Blang Karieng Village, which numbered 36 children. Sampling was carried out using total sampling techniques totaling 35. This study was from April 2018, using a questionnaire as a research instrument. The results showed that simultaneously there was a significant effect of the independent variables on the dependent variable with a value of sig <Î± (0.05). While partially the most influential variables on child cooperatives are authoritarian and permissible variables with a p-value of 0.085. The conclusion of this study, it can be concluded that there is a significant effect of parenting on the cooperative level of children aged 3-5 years in dental and oral care.